ADEA‐ADEE Shaping the Future of Dental Education III: Engaging with global networking to enable global oral health. Issue 1 (24th January 2020) - Patel, Upen S.; Shapira, Lior; Gallagher, Jennifer E.; Davis, Joan; Garcia, Lily T.; Valachovic, Richard W.
Abstract: Global networking has been identified as an important method of enhancing health care education and services in the field of dentistry. 1 The ability to share expertise, resources, knowledge, and experience to benefit all is highly desired among students, educators, health care professionals, and communities globally. Both our student and patient populations are dynamic societies that are becoming increasingly complex and facing growing needs and expectations, which is a constant challenge for educators and health care professionals to satisfy. 2 The key question, stemming from the Global Networking (GN) workshop of the 2017 ADEE‐ADEA Shaping the Future of Dental Education II meeting, was identified as, "How can dental educators around the world network to share ideas, experience, expertise, and resources to improve our curricula and teaching and learning environments for our educators, students, and communities that they serve?" The action plan devised by the GN workshop from the 2017meeting indicated two key steps in these early stages of setting up a global network: 1) "…grassroots participation for input and consumption of meaningful and needed content, " and 2) "…advisors/consultants for organizational top‐down guidance to define and maintain the global networking philosophy and platform…". 1 The GN workshop of 2019 SFDE meeting aimed to deliver guidance and discussion with those experienced in engaging local communities from both a grassroots and an organizational approach.